2020
DOI: 10.21876/rcshci.v10i2.937
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Burnout em enfermeiros trabalhadores de um hospital público de Natal, Rio Grande do Norte, Brasil

Abstract: Objetivo: O termo “burnout” descreve uma síndrome desenvolvida em pessoas expostas a situações de estresse laboral de forma crônica. Dentre as profissões do setor público no âmbito da saúde, a enfermagem é considerada a quarta mais estressante. O objetivo deste trabalho foi avaliar a prevalência da Síndrome de Burnout (SB) em enfermeiros do Hospital Monsenhor Walfredo Gurgel de Natal/RN. Métodos: Estudo quantitativo, transversal e analítico, de caráter prospectivo em 80 enfermeiros(as) no período de julho a ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
2
0
2
Order By: Relevance
“…In line with this perception, most nurses analyzed in the present study report having two jobs, corresponding to 59% of the sample, and 5% who report having three jobs, a condition directly correlated to the personal burnout dimension, with a significant correlation identified. These findings corroborate the descriptions by Freitas and Freire 17 of nursing workers at a public hospital in Natal/RN, indicating that this is a trend amongst nursing professionals in the State's public sphere.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with this perception, most nurses analyzed in the present study report having two jobs, corresponding to 59% of the sample, and 5% who report having three jobs, a condition directly correlated to the personal burnout dimension, with a significant correlation identified. These findings corroborate the descriptions by Freitas and Freire 17 of nursing workers at a public hospital in Natal/RN, indicating that this is a trend amongst nursing professionals in the State's public sphere.…”
Section: Discussionsupporting
confidence: 90%
“…A widely used instrument for characterizing BS is the Copenhagen Burnout Inventory (CBI) 16,17 , which defines the syndrome based on three dimensions: personal, work-related, and patient-related. Personal…”
Section: Introductionmentioning
confidence: 99%
“…Estudo realizado por Rodrigues et al (2017), no nordeste brasileiro, reforça tal ocorrência, em que 61,9% dos profissionais apresentam duplo vínculo empregatício. Cabe salientar que a presença de mais vínculos empregatícios aumenta a carga horária semanal e diminui o tempo de descanso do profissional, o que favorece a ocorrência de desgaste físico e psíquico (Freitas & Freire, 2020).…”
Section: Discussionunclassified
“…Studies carried out with nurses in Paraíba and Rio Grande do Norte identified moderate levels of work-related burnout, demonstrating a correlation between this and workload. Notably, preventive measures for these professionals' health are necessary to avoid their illness 32,33 .…”
mentioning
confidence: 99%